Serodiagnosis of Human Cutaneous Anthrax in India Using an Indirect Anti-Lethal Factor IgG Enzyme-Linked Immunosorbent Assay - Ghosh, N. (American Society for Microbiology, 2013)
Anthrax, caused by Bacillus anthracis, is primarily a zoonotic disease. Being a public health problem also in several developing countries, its early diagnosis is very important in human cases. In this study, we describe the use of an indirect enzyme-linked immunosorbent assay (ELISA) for detection of anti-lethal factor (anti-LF) IgG in human serum samples. A panel of 203 human serum samples consisting of 50 samples from patients with confirmed cutaneous anthrax, 93 samples from healthy controls from areas of India where anthrax is nonendemic, 44 samples from controls from an area of India where anthrax is endemic, and 16 patients with a disease confirmed not to be anthrax were evaluated with an anti-LF ELISA. The combined mean anti-LF ELISA titer for the three control groups was 0.136 ELISA unit (EU), with a 95% confidence interval (CI) of 0.120 to 0.151 EU. The observed sensitivity and specificity of the ELISA were 100% (95% CI, 92.89 to 100%) and 97.39% (95% CI, 93.44 to 99.28%), respectively, at a cutoff value of 0.375 EU, as decided by receiver operating characteristic (ROC) curve analysis. The likelihood ratio was found to be 49.98. The positive predictive value (PPV), negative predictive value (NPV), efficiency, and Youden's index (J) for reliability of the assay were 92.5%, 100%, 98.02%, and 0.97, respectively. The false-positive predictive rate and false-negative predictive rate of the assay were 2.61% and 0%. The assay could be a very useful tool for early diagnosis of cutaneous anthrax cases, as antibodies against LF appear much earlier than those against other anthrax toxins in human serum samples.